Role of unified modelling language in software development in Greece – results from an exploratory study. Issue 4 (1st August 2014) - Fitsilis, Panos; Gerogiannis, Vassilis C.; Anthopoulos, Leonidas
Abstract : The Unified Modelling Language (UML) is a language for specifying, visualising, constructing and documenting software systems. The UML proved to be extremely successful and it has achieved tremendous popularity making it the de facto industry standard for object oriented system development. As such, many researchers presented empirical studies on the practical usage of UML but as well criticisms for UML complexity, difficulty to be learnt, etc. Even though a large number of articles and books are devoted to various aspects of UML language, there is little evidence on how UML is used. This study attempts to identify the profile of persons using UML, to pinpoint UML diagrams that are being used and their effectiveness, to discover whether CASE tools are being used and to record the perceived usefulness of UML language. For conducting the study a survey was developed and it was distributed to mailing lists of Greek IT professionals and to university students. The findings indicate that UML is used successfully in the majority of software development projects and that most users perceive UML positively since it supports faster system building, development of higher quality software systems, and for specific cases, it leads to software development cost‐decrease.